Effect of cholymbi on growth, proximate composition, and digestive enzyme activity of fingerlings of Long whiskered catfish, Mystus gulio (actinopterygii: siluriformes: bagridae) - Rajkumar, Mayalagu; Rahman, Mohammad Mustafizur; Reni Prabha, Arockiasamy; Phukan, Bipul (The West Pomeranian University of Technology in Szczecin, 2013)
Background. Long whiskered catfish, Mystus gulio (Hamilton, 1822), enjoys a high consumer preference and market demand in many Asian countries including India. However, the growth of this fish is very slow under normal aquaculture conditions. The non-hormonal growth promoter—cholymbi—which contains minerals and the essential amino acids lysine and methionine, is widely used in livestock and poultry as a feed additive to improve growth and survival. Supplementing feed with cholymbi may increase the growth and survival of Mystus gulio. Materials and methods. A feeding trial was conducted to determine the effect of dietary cholymbi supplementation on growth, survival, and feed conversion ratio of long whiskered catfish fingerlings. Four isoproteic diets (crude protein 37%) were formulated to incorporate cholymbi at 0%, 0.25%, 0.50%, and 0.75% diet. The diets were fed to triplicate groups of fish twice daily to supply 5% of the total body weight per day for 120 days. Water quality parameters were maintained within the range suitable for catfish growth. Results. Weight gain (WG), protein efficiency ratio (PER) and feed conversion ratio (FCR) were all affected by diet (P < 0.01, 0.001, and 0.001, respectively). The group fed the 0.50% cholymbi diet had the highest WG and PER and the lowest FCR, although not significantly different from the group fed the 0.25% cholymbi diet. There was no significant difference (P > 0.05) in carcass proximate composition of catfish fed diets containing these different levels of cholymbi. Gut protease, amylase, and lipase activities were stimulated by dietary inclusion of cholymbi at all levels compared to control. Conclusion. As cholymbi is a newly introduced dietary supplement for fish, more research is needed to optimize its supplementation to improve growth, PER, FCR, and survival of long whiskered catfish. Until then, a diet with 0.50% cholymbi can be recommended to improve the aquaculture production of this species.